2023
DOI: 10.1021/acsestwater.2c00548
|View full text |Cite
|
Sign up to set email alerts
|

Application of Supercritical Water Oxidation to Effectively Destroy Per- and Polyfluoroalkyl Substances in Aqueous Matrices

Christopher G Scheitlin,
Kavitha Dasu,
Stephen Rosansky
et al.

Abstract: Supercritical water oxidation (SCWO) is a destruction technology to treat per- and polyfluoroalkyl substance (PFAS)-impacted groundwater, investigation-derived waste, and other aqueous matrices such as landfill leachate and aqueous film-forming foam. A SCWO system, Battelle’s PFAS AnnihilatorTM, was optimized with a goal of reducing all measured PFAS to non-detect levels. Laboratory-prepared and field-collected samples with inlet PFAS concentrations up to 50 ppm were consistently destroyed to less than 70 ppt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Supercritical water is achieved at temperatures and pressures above its critical point (374°C and 22.1 MPa). At higher temperatures, around 575°C–650°C, nearly all PFASs can be mineralized with a residence time of 25 s (Li, Austin, et al, 2023; McDonough et al, 2022; Scheitlin et al, 2023). Destruction percentages are largely impacted by the temperature of the reactor (Scheitlin et al, 2023).…”
Section: Destruction Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Supercritical water is achieved at temperatures and pressures above its critical point (374°C and 22.1 MPa). At higher temperatures, around 575°C–650°C, nearly all PFASs can be mineralized with a residence time of 25 s (Li, Austin, et al, 2023; McDonough et al, 2022; Scheitlin et al, 2023). Destruction percentages are largely impacted by the temperature of the reactor (Scheitlin et al, 2023).…”
Section: Destruction Technologiesmentioning
confidence: 99%
“…At higher temperatures, around 575°C–650°C, nearly all PFASs can be mineralized with a residence time of 25 s (Li, Austin, et al, 2023; McDonough et al, 2022; Scheitlin et al, 2023). Destruction percentages are largely impacted by the temperature of the reactor (Scheitlin et al, 2023). Commercial SCWO reactors are operated at temperatures >500°C to ensure complete destruction and reduce the residence time.…”
Section: Destruction Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors confirmed the previously established fact that the pressure did not significantly affect the efficiency of the process. Groundwaters contaminated with polyfluoroalkyl compounds (PFAS) were treated at high temperatures (≥600 • C) with supercritical water oxidation (SCWO), achieving complete combustion and producing carbon dioxide, water, and corresponding anion acids, and were considered safe after neutralization [9]. In steady conditions, after 3 h of treatment, the concentration of PFAS dropped from ~50 ppm level to an almost undetectable level (70 ppt).…”
Section: Introductionmentioning
confidence: 99%